Respostas
respondido por:
1
x 3 2 x²+3+30-2x-3x-15-12=0 x=-b+-√Δ/2
5 x 1 = 12 x²-5x+6=0 x=-(-5)+-/2*1
1 3 1 Δ=b²-4*ac x=5+-1/2
Δ=(-5)²-4*1*6 x'=5+1/2 x''=5-1/2
x 3 2 x 3 Δ=25-24 x'=3 x''=2
5 x 1 5 x = 12 Δ=1
1 3 1 1 3
5 x 1 = 12 x²-5x+6=0 x=-(-5)+-/2*1
1 3 1 Δ=b²-4*ac x=5+-1/2
Δ=(-5)²-4*1*6 x'=5+1/2 x''=5-1/2
x 3 2 x 3 Δ=25-24 x'=3 x''=2
5 x 1 5 x = 12 Δ=1
1 3 1 1 3
Anônimo:
obrigadoooo di nvo;)
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás